An Empirical Investigation of Mental Illness, Impostor Syndrome, and Social Support in Management Doctoral Programs. (February 2021) - Pervez, Adam; Brady, Lisa L.; Mullane, Ken; Lo, Kevin D.; Bennett, Andrew A.; Nelson, Terry A.
Scholars in multiple cross-disciplinary studies have found rates of mental illness among graduate students exceed the reported averages. Yet mental illness among management doctoral students remains largely unexplored. In this study, we surveyed 113 management doctoral students to ascertain the prevalence of symptoms for two common mental illnesses, depression and anxiety, as well as experiences of impostor syndrome and perceived sources of social support. Empirical findings from the first phase of our research suggest that management doctoral students are at greater risk than the general population of experiencing symptoms of depression, anxiety, and feelings of being an impostor. However, social support from a supervisor and from friends was negatively related to symptoms of depression and anxiety, indicating that these sources can be helpful. In phase two of our research, a thematic analysis of data from structured interviews with nine management doctoral students revealed themes linking impostor syndrome with social support, highlighting that the type of social support may be as beneficial as the source of social support. Recommendations for future research, as well as for students, supervisors, and administrators, are provided.